PENGARUH KEPUASAN KONSUMEN TERHADAP GETOK TULAR (Studi Empiris: Wisatawan Mancanegara Pantai Kuta-Bali) - Chandra Wibowo Widhianto; Henilia Yulita (Program Studi Hospitality dan Pariwisata, 2017)
Bali is a tourism that is recognized by the whole world in natural beauty and the thickcultural richness. Kuta Beach-Bali is also one of the best ten beaches in the world(Made, 2010). This research took the title